Cystography Helps Shorten Urethral Catheterization Time after Radical Retropubic Prostatectomy - Sittiporn Srinualnad; Suthipol Udompunturak; Chaiyong Nualyong (Siriraj Medical Journal, 2005)
Objective: Post operative urethral drainage after radical retropubic prostatectomy is bothersome to patients. We assessed theÂ possibility of using cystography to determine the feasibility and safety of early removal of urinary catheter. Methods: 56 patients who underwent radical retropubic prostatectomy from February 2001- December 2004 by one surgeon using one operative technique were reviewed. Cystography was performed on post-operative day 7 in the last 14 consecutive cases (group 1). The control group included 42 patients who had the urinary catheter removed 14 days postoperatively without cystography (group 2). In group 1, the urinary catheter was removed if cystogram showed no contrast media leakage. Data of the operations, pathological reports, complications and incontinence rate were compared between the two groups. Results: In group 1, the urinary catheter was removed on post-operative day 7 in 71% of the patients. The median catheterization time was 7 days and 14 days in group 1 and group 2, respectively (p<0.001). The incontinence rate was not significantly different in the two groups. There was no voiding difficulty or urinary retention reported in group 1. Conclusion: Cystography alleviates urethral discomfort after radical retropubic prostatectomy by shortening urinary catheterization time. Cystography should be considered in all patients who undergo radical retropubic prostatectomy on post-operative day 7. A meticulous urethrovesical anastomosis is required to reduce urinary catheterization time.